The Neurobiology of Infant Attachment-Trauma and Disruption of Parent–Infant Interactions - Naeem, Nimra; Zanca, Roseanna M.; Weinstein, Sylvie; Urquieta, Alejandra; Sosa, Anna; Yu, Boyi; Sullivan, Regina M. (Frontiers in Behavioral Neuroscience, 2022)
Current clinical literature and supporting animal literature have shown that repeated and profound early-life adversity, especially when experienced within the caregiver-infant dyad, disrupts the trajectory of brain development to induce later-life expression of maladaptive behavior and pathology. What is less well understood is the immediate impact of repeated adversity during early-life with the caregiver, especially since attachment to caregiver occurs regardless of the quality of care the infant received including experiences of trauma. The focus of the present manuscript is to review the current literature on infant trauma within attachment, with an emphasis on animal research to define mechanisms and to translate developmental child research. Across species, the effects of repeated trauma with the attachment figure, are subtle in early-life, but the presence of acute stress can uncover some pathology, as was highlighted by Bowlby and Ainsworth in the 1950’s. Through rodent neurobehavioral literature we discuss the important role of repeated elevations in stress hormone corticosterone (CORT) in infancy, especially if paired with the mother (not when pups are alone) as targeting the amygdala and causal in infant pathology. We also show that following induced alterations, at baseline infants appear stable, although acute stress hormone elevation uncovers pathology in brain circuits important in emotion, social behavior, and fear. We suggest that a comprehensive understanding of the role of stress hormones during infant typical development and elevated CORT disruption of this typical development will provide insight into age-specific identification of trauma effects, as well as a better understanding of early markers of later-life pathology.